(untitled) (CAHIERS MAGELLANES-NS, 2024)
The presence of Extended Spectrum Beta-Lactamase (ESBL) bacteria in nosocomial infections and community-acquired disorders presents a serious threat to public health. The frequency, identification, and characterization of ESBL-producing bacteria in municipal water systems are examined in this review. Treatment efforts are complicated by the resistance mechanisms of ESBL bacteria, which have been brought about by the extensive use of beta-lactam antibiotics. Municipal water supplies, which are necessary for community survival, are coming under more and more scrutiny as possible harbours for these bacteria resistant to drugs. The prevalence rates of ESBL-producing bacteria in municipal water systems across the world are explained in this article, which also provides information on the various genetic backgrounds and antibiotic resistance profiles of these bacteria. Techniques for identification are essential for distinguishing ESBL bacteria from the diverse microbial environment found in water sources. This study addresses the benefits and drawbacks of several identification tactics, ranging from traditional culture-based approaches to cutting-edge molecular techniques like PCR and whole-genome sequencing. The investigation also explores cutting-edge technologies like metagenomics, which provide a thorough understanding of the microbial community and reveal the hidden variety of ESBL bacteria in these habitats.